COMPARISON OF MASSAGE THERAPY AND PASSIVE STRETCHING FOR REDUCING DOMS OF TIBIALIS ANTERIOR - Rehman, Ateeb; Sadiq, Noman; Khan, Asghar (European Journal of Health Sciences, 2021)
Purpose: To find the effect of massage therapy in comparison with static stretching for reducing DOMS in tibialis anterior muscle and to assess their effect on performance of athletes with these therapies. Methodology: An experimental study was done in Imperial University Lahore for the duration of 06 months from 15 August to February 15. Participants were selected through non-probability convenience sampling technique as per inclusion criteria. Sample size was 40, from which participants were equally divided into two groups; Group-A (massage therapy) and Group-B (static stretching). DOMS were induced in tibialis anterior mucle and assessments was carried out before intervention and after applying intervention using NPRS, vertical jump height test, and sprint speed test. Findings: Both massage therapy and passive static stretching techniques were found to be effective for reducing the muscle soreness in the tibialis anterior muscle, as well as for improving players' performance. However, within group analysis shows that passive static stretching significantly improves the vertical jump height and sprint speed duration in the athletes. Unique contribution to theory, practice and policy: The literature regarding the comparison of two techniques (massage & passive static stretching) is lacking especially their effect on tibialis anterior. This study fills the gap and will guide sports rehabilitators and trainers to devise better intervention strategies for countering the symptoms of DOMS and its effects on performance.